2020
DOI: 10.1002/acn3.50987
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in multiple system atrophy: a single‐center cohort study

Abstract: Objective Cognitive impairment in multiple system atrophy (MSA) is common, but remain poorly characterized. We evaluated cognitive and behavioral features in MSA patients and assessed between‐group differences for MSA subtypes and the effect of orthostatic hypotension (OH) on cognition. Methods This retrospective study included 54 patients with clinical diagnosis of possible and probable MSA referred to the Department of Neurology at Medical University of Innsbruck between 2000 and 2018. Neurological work‐up i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 71 publications
5
25
2
Order By: Relevance
“…Recent studies found that a varying degree of cognitive impairment was common in MSA assessed by comprehensive neuropsychological testing. [33,34] Our current study found that cognitive impairment was the determinant of health utility value in MSA-P but not in MSA-C. [35,36] Kawai reported that patients with MSA-P had wider and severer cognitive impairment than patients with MSA-C. [35] Patients with MSA-P were reported to have lower MoCA scores than patients with MSA-C in a Chinese study. [37] Additionally, we found that frontal lobe dysfunction was the determinant of EQ-VAS score in MSA-P but not in MSA-C, which was similar to our previous nding that frontal lobe dysfunction was the determinant of HRQoL assessed by PDQ-39 in MSA.…”
Section: Discussionmentioning
confidence: 44%
“…Recent studies found that a varying degree of cognitive impairment was common in MSA assessed by comprehensive neuropsychological testing. [33,34] Our current study found that cognitive impairment was the determinant of health utility value in MSA-P but not in MSA-C. [35,36] Kawai reported that patients with MSA-P had wider and severer cognitive impairment than patients with MSA-C. [35] Patients with MSA-P were reported to have lower MoCA scores than patients with MSA-C in a Chinese study. [37] Additionally, we found that frontal lobe dysfunction was the determinant of EQ-VAS score in MSA-P but not in MSA-C, which was similar to our previous nding that frontal lobe dysfunction was the determinant of HRQoL assessed by PDQ-39 in MSA.…”
Section: Discussionmentioning
confidence: 44%
“…Overt dementia is considered an exclusion criterion for the diagnosis of MSA, nevertheless cognitive impairment may occur, especially in the advanced disease stages (Eschlböck et al 2020 ). Regarding cognitively impaired MSA patients, concomitant amyloid-plaques, tau and LB co-pathology have been reported (Jellinger 2020 ).…”
Section: Neuropathologymentioning
confidence: 99%
“…However, the presence of cognitive decline among MSA patients who undergo neuropsychological assessment has been also reported at disease onset and, in some patients, the cognitive impairment has preceded motor impairment [108]. Studies on cognitive function in MSA not only disclosed a broad spectrum of deficits in cognition and behavior describing frequently a profile that can be similar to that seen in PD and DLB, with predominant deficits in processing speed, verbal memory, and executive function [109,110], but visuospatial and constructional dysfunction have also been reported [111]. Similar to PD, MMSE does not seem sufficient to assess cognition in these patients [112] and MoCA seems to be more sensitive to detect the mild cognitive decline in MSA [113].…”
Section: Cognitive Dysfunction Across α-Synucleinopathiesmentioning
confidence: 99%